Genetic Variability and Heritability Estimates of Growth and Yield Component of Curly Chili Pepper - Anira, Rayuli; Herison, Catur; Suryati, Dotti (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2017)
Success in a breeding program is primarily determined by the availability of information about the genetic diversity of the genetic material used and the expected heritability of the character to be improved. The objective of this study was to determine genetic diversity and heritability of growth and yield components of 10 curly chili genotypes. This research was conducted in September 2015 - February 2016 in the Medan Baru field experiment of Faculty of Agriculture at Kandang Limun Village, Muara Bangkahulu Subdistrict, Bengkulu City. The experiment was arranged in Completely Randomized Design (CRD) with ten genotypes and six replications. The genotypes used were Local Payakumbuh, Ferosa, Laris, Kopay, Romario, Keriting Hitam, Local Curup, Bogota, Sempurna and Mario. The results showed that genetic diversity of the ten varieties was narrow based on plant height variables, dichotomous height, stem diameter, flowering age, harvest age, fruit length, fruit diameter, weight per fruit and number of fruits. Stem diameter, fruit length, fruit diameter and weight per fruit had moderate heritability estimates; meanwhile, anthesis and number of fruits showed low heritability.